Application of Semi-Permanently Installed Optical Fiber Outside the Tubing in Offshore Heavy Oil Steam Huff and Puff Thermal Recovery Blocks - CHI Ming; CHEN Jianbo; WANG Haipeng; ZHAO Yun; WANG Guiyu; ZHAO Yungang; WANG Xiaolong; WANG Longxiang (Cejing jishu, 2025)
In the heavy oil steam huff and puff thermal recovery blocks of Yuedong island, Liaohe oilfield, dynamic monitoring of production profiles in individual wells is required. Traditional wireline logging cannot be effectively applied in such blocks due to challenges including high temperature, high pressure, high-viscosity crude, high wax content, and frequent immobilization of flowmeter probes by viscous crude. As the Liaohe oilfield enters its mid-to-late development stages, severe water production in wells has made water shutoff and production enhancement critical to improving oil recovery. Consequently, developing novel technologies for enhanced production profile monitoring in heavy oil thermal recovery blocks has become imperative. To address the low success rate of logging in heavy oil thermal recovery wells, a semi-permanently installed optical fiber outside the tubing (SPOFT) logging technology has been developed by integrating the advantages of tubing-conveyed deployment (immune to high-viscosity crude) with high-temperature optical cables (enabling long-term monitoring, full-wellbore data acquisition, and thermal resistance). This technology comprises, high-temperature resistant optical cables, cable protection clamps, long-term fiber optic monitoring cabinets, secondary fiber optic sealing boxes, fiber bragg grating (FBG) sensors, FBG sealing devices, protective carrier tubes for sealing devices, modified tubing hangers and flange penetrations, and mechanical sealing heads. Leveraging the intrinsic high-temperature resistance of polyimide-coated optical cables and their high-precision real-time measurement capabilities, the cables are deployed synchronously with tubing installation to target depths, enabling long-term temperature and pressure data acquisition. By replacing traditional wireline logging methods (spot measurements or continuous logging), this technology overcomes the limitations of conventional logging in heavy oil thermal recovery blocks. It achieves real-time, full-wellbore monitoring of reservoir parameters such as temperature, acoustic noise, and pressure, providing critical insights for optimizing reservoir development strategies.